Growth and accumulation of flavan-3-ol in Camellia sinensis through callus culture and suspension culture method - Sutini Sutini; Susilowati Susilowati; M. Rasjad Indra; Djoko Agus Purwanto (The East Java Biological Society, 2016)
This study was aimed to assess flavan-3-ol biomass in C. sinensis through callus cultures and suspension cultures derived from leaf explants. Callus initiation of both cultures were using Murashige and Skoog medium were enriched with plant growth regulators Naphthalene Acetic Acid 3.0 mg/L and kinetin 2.0 mg/L. The procedures in this study were: (1) callus initiation by cutting the leaves of C. sinensis shoots then planted on Murashige and Skoog medium that were enriched with plant growth regulators, (2) sub callus culture on fresh medium that enriched with the same growth regu-lators, (3) suspension culture initiation of liquid callus, (4) growth examination of callus and suspension cultures in week 12, (5) examination of qualitative-quantitative content of flavan-3-olin suspension cultures at week 4. The results show that suspension cultures contain biomass flavan-3-ol that increase in the same manner of the increase of callus age and weight.